2010
DOI: 10.1111/j.1537-2995.2010.02763.x
|View full text |Cite
|
Sign up to set email alerts
|

Relapsing or refractory idiopathic thrombotic thrombocytopenic purpura‐hemolytic uremic syndrome: the role of rituximab

Abstract: Idiopathic thrombotic thrombocytopenic purpura-hemolytic uremic syndrome (TTP-HUS) is a rare disease responsive to treatment with plasma exchange (PE) but with a high percentage of relapse or refractory patients. A severe deficiency of ADAMTS-13 (<5% of normal activity), congenital or caused by an autoantibody, may be specific for TTP and it has been proposed that severe ADAMTS-13 deficiency now defines TTP. B cells play a key role in both the development and the perpetuation of autoimmunity, suggesting that B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 68 publications
(194 reference statements)
1
48
0
3
Order By: Relevance
“…[34][35][36][37] Most of the data are based on case reports and case series where rituximab was used concomitantly with other immunosuppressive agents. 23,34,[36][37][38][39][40][41][42] A recent thoughtful review on this topic adds some clarity to its use in this clinical situation.…”
Section: Rituximabmentioning
confidence: 99%
“…[34][35][36][37] Most of the data are based on case reports and case series where rituximab was used concomitantly with other immunosuppressive agents. 23,34,[36][37][38][39][40][41][42] A recent thoughtful review on this topic adds some clarity to its use in this clinical situation.…”
Section: Rituximabmentioning
confidence: 99%
“…The diagnosis of PRES includes the presence of neurological symptoms such as seizure, headache, encephalopathy, and visual disturbances, in addition to radiologic findings on brain MRI of focal vasogenic edema [1][2][3][4][5][6][7]. The syndrome was described in association with acute hypertension, preeclampsia or eclampsia, renal disease, sepsis, and exposure to immunosuppressive agents [8][9][10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that, in patients with primary refractory or relapsing de novo TTP-HUS, administration of intravenous immunoglobulin, anti-CD20 antibody, rituximab, and belatacept in combination with plasma exchange may also had some benefits in terms of improvment (16)(17)(18)(19). These drugs were not available in our center and we do not have access to them.…”
Section: Discussionmentioning
confidence: 93%